Envenomation: an uncommon cause of respiratory distress in a neonate - A, Arul Kumaran; N, Dinesh Kumar; R, Anu Priya; S, Balaji (International Journal of Contemporary Pediatrics, 2017)
Respiratory distress in a neonate is a common problem in our practice. The causes may be respiratory, cardiovascular, metabolic, haematological, surgical and central. However in late neonatal period is often due to pneumonia, metabolic or cardiac. We report an uncommon cause of acute respiratory distress in a 26 day old neonate due to myocarditis secondary to scorpion sting envenomation who recovered with our early diagnosis and prompt treatment.